Expression of Villin associated with Epithelial to Mesenchymal Transition in patients with gastric cancer relating to their clinical and morphological specifications - Azizi, Seyed Mohammad; Hashemi, Mehrdad; Falsafi, Sarvenaz; Azizi, Seyedeh Mina; Shirkoohi, Reza (Asian Pacific Journal of Cancer Biology, 2020)
Aim and Background: Gastric cancer is the fourth most common cancer in the world and the second leading cause of cancer-related deaths. The metastatic invasive cells of tumor tissue are the main cause of mortality. Numerous biological phenomena are involved in organizing the metastatic process. The Epithelial to Mesenchymal Transition is one of the major mechanisms modulating malignant phenotypes by gastric epithelial cells. Specific cell signals are responsible for epithelial or mesenchymal maintenance of the cells in the tissue. These signals are evaluated by measuring the expression of epithelial and mesenchymal biomarkers in that tissue. Villin is an actin-binding protein mainly expressed in the brush border of epithelium which preserves the shape of the cell and its adhesion to the tissue. The aim of the present research is to study the expression of Villin in the cells as a feasible epithelial biomarker in order to evaluate the cross-sectional situation of the cells. Materials and Methods: 38 patients with gastric cancer that were admitted to the Cancer Institute of Imam Khomeini in a period of 6 months were chosen randomly. two samples were collected from each individual; one from the tumoral tissue and one from normal margin of the tumorous tissue. These samples were evaluated after obtaining informed consent from the patients. RNA was extracted from the samples and used as template for cDNA synthesis. The Villin expression was then measured through Real-Time PCR and statistical data according to tissue type and different grades were collected. Results: The expression of Villin in tumor tissue of the patients with gastric cancer was significantly lower than the normal tissue. Conclusion: As it appears decreased expression of Villin can act as an effective factor toward loss of epithelial nature of the cell and occurring Epithelial to Mesenchymal Transition followed by metastasis.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">